Toll receptor-mediated Hippo signaling controls innate immunity in Drosophila - Liu, Bo (Cell, 2016)
The Hippo signaling pathway functions through Yorkie to control tissue growth and homeostasis. How this pathway regulates non-developmental processes remains largely unexplored. Here we report an essential role for Hippo signaling in innate immunity whereby Yorkie directly regulates the transcription of the Drosophila IκB homologue, Cactus, in Toll receptor-mediated antimicrobial response. Loss of Hippo pathway tumor suppressors or activation of Yorkie in fat bodies, the Drosophila immune organ, leads to elevated cactus mRNA levels, decreased expression of antimicrobial peptides and vulnerability to infection by Gram-positive bacteria. Furthermore, Gram-positive bacteria acutely activate Hippo-Yorkie signaling in fat bodies via the Toll-Myd88-Pelle cascade, through Pelle-mediated phosphorylation and degradation of the Cka subunit of the Hippo-inhibitory STRIPAK PP2A complex. Our studies elucidate a Toll-mediated Hippo signaling pathway in antimicrobial response, highlight the importance of regulating IκB/Cactus transcription in innate immunity, and identify Gram-positive bacteria as extracellular stimuli of Hippo signaling under physiological settings.